2022
DOI: 10.3390/buildings12020211
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Untreated Fine Sediments as Filler: Is It More Beneficial than Incorporating Them as Sand?

Abstract: Large amounts of sediments are dredged each year to ensure navigation. These materials, classified as waste, seem to be promising alternatives to conventional construction materials. Dredging operations, carried out by the Territorial Directorate of the Seine Basin (DTBS), generate an annual volume of sediments of about 150,000 m3, of which nearly 50% are fine sediments (<80 μm). For these fine sediments, it is necessary to look for possible ways of valorisation, knowing that the coarse sediments, sands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…These results align with the research conducted by Moradi and Shahnoori, where the compressive strength of concrete specimens was negatively impacted when the marine sediment content exceeded 15% [8]. According to Bedaa et al, the decrease in the mechanical strength of concrete made with marine sediment as partial substitute of sand can be attributed to the fine particles of sediments which affect the properties of cement paste, as well as the chemical composition of marine sediment (i.e., salt content) [35]. However, concrete specimens made with 30% of marine sediment achieve the targeted mechanical strength of 38 MPa at 28 days.…”
Section: Effect Of Marine Sediment On the Hardened State Of Sccsupporting
confidence: 87%
See 1 more Smart Citation
“…These results align with the research conducted by Moradi and Shahnoori, where the compressive strength of concrete specimens was negatively impacted when the marine sediment content exceeded 15% [8]. According to Bedaa et al, the decrease in the mechanical strength of concrete made with marine sediment as partial substitute of sand can be attributed to the fine particles of sediments which affect the properties of cement paste, as well as the chemical composition of marine sediment (i.e., salt content) [35]. However, concrete specimens made with 30% of marine sediment achieve the targeted mechanical strength of 38 MPa at 28 days.…”
Section: Effect Of Marine Sediment On the Hardened State Of Sccsupporting
confidence: 87%
“…The amount of binder and filler used in the SCC mix design decreased by 10% and 45%, respectively when marine sediment was used. This results in a reduction in the CO 2 emissions of SCC made with marine sediment [35]. Given that CO 2 emission per kilogram of cement production falls within the range of 0.5 to 0.9, a reduction of 15 kg (10%) of cement in the SCC made with marine sediment would result in a decrease of at least 7.5 kg of CO 2 emissions per ton of this concrete [36].…”
Section: Influence Of Marine Sediment On the Fresh State Of Sccmentioning
confidence: 99%
“…Dredged sediment can be used as an alternative source of conventional aggregate used for the manufacture of concrete or mortar [24,60,[71][72][73][74] by acting as a substitute for sand. It can also partially replace raw materials for cement production [75][76][77]; this often requires adequate treatment before use. More studies have focused on the reuse of dredged sediment as foundation or base layers in road engineering [34,[78][79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete samples based on nine formulations are tested to study the effect of incorporating dredged sand on slump, hydration, and compressive strength. On the one hand, similar studies have shown the possibility of incorporating marine sediments into concrete without significantly affecting the properties of the concrete, which makes it possible to reduce the carbon footprint and the cost of concrete [17][18][19][20][21][22]. On the other hand, Hassoune et al [23] showed the interest of using concrete formulations based on dredged sand in the manufacture of tetrapods for the protection of harbor breakwaters.…”
Section: Introductionmentioning
confidence: 99%